Vico's Critique of Cartesian Thought as one of the most important beginings of the emergence of historical thinking - Maryam Darbanian; Bijan Abdolkarimi (Journal of Philosophical Investigations, 2022)
As a pioneer of historical thinkers, Vico laid out the origins of his historical thought in his critique of Cartesian mathematicalism. Descartes' effort, is not to attain the truth, but to attain certainty with the criterion of clarity and distinction. He sought to make all the sciences sure in this way. On the base of this point of view, all humanities, including history are excluded from the sphere of sciences, which means forgetting much heritage of the past. Vico considers Descartes’ unhistorical and static understanding of human nature as the most important philosophical problem of French philosopher. For Vico the nature of man and consequently his thinking and Reason have transformed throughout the history. Vico justifies this transformation in different periods of history with corresponding forms of reasoning. On the base of his epistemological rule, namely “the real is constructive”, Vico conceives making something as the condition of knowing it. Therefore, he believes that history and all human achievements, are man-made and intrinsically constructed and hence are recognizable through empathetic insight and the power of imagination. Vico believes that the outcome of Cartesian philosophy is nothing other than human being’s disconnection from history and society. For Vico, the true knowledge of everything is knowledge through its causes or, in other words, historical knowledge about it. Although Vico considers history as the result of man-made activites, he conceives divine providence as the leader and guide of history. In Vico's view, understanding history in any given period is possible through a proper understanding of the intellectual framework and principles governing that period.